Patellar fracture nonunion treated without reosteosynthesis: Case report - Abdulelah K. Alqawlaq; Abeer O. Ismail; Mohammad Maddah (Radiology Case Reports)
Patellar fractures are common injuries often managed with open reduction and internal fixation (ORIF); however, nonunion is a rare complication, with an incidence of 2.4%-12.5%. This case report describes a 26-year-old male who sustained a comminuted patellar fracture in a road traffic accident and subsequently developed nonunion despite having a good range of motion and normal extension strength. He presented with persistent knee pain, and imaging confirmed the nonunion. Surgical removal of tension band wiring and cerclage was performed, revealing strong fibrous connections between the fracture fragments, and reosteosynthesis was deemed unnecessary. Postoperatively, the patient experienced complete pain relief and full functional recovery. This case highlights the importance of individualized treatment plans, demonstrating that not all cases of patellar nonunion require reosteosynthesis if the extensor mechanism remains intact, and that hardware removal alone can be an effective treatment strategy.